2018
DOI: 10.1111/lam.12881
|View full text |Cite
|
Sign up to set email alerts
|

Low-cost biotransformation of glycerol to 1,3-dihydroxyacetone throughGluconobacter frateuriiin medium with inorganic salts only

Abstract: This study illustrates the advantages of inorganic nutrients supplementation over organic nutrient supplementation for a lower media cost and a higher dihydroxyacetone (DHA) production yield through Gluconobacter frateurii BCC 36199 cultivation. The study found that the use of media that contain only glycerol and inorganic salts enhanced DHA production (DHA-Prod) while keeping the production of bacterial biomass at a sufficient level. Most of the starting material, that is, glycerol, is converted into DHA, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Table shows that every 1 kg of refined glycerol can produce 0.97 kg of DHA ( y sp = 99%). Given that the price of DHA is 25 USD kg −1 , this results in a profit of 23.01 USD per 1 kg of glycerol.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table shows that every 1 kg of refined glycerol can produce 0.97 kg of DHA ( y sp = 99%). Given that the price of DHA is 25 USD kg −1 , this results in a profit of 23.01 USD per 1 kg of glycerol.…”
Section: Resultsmentioning
confidence: 99%
“…The production cost can be decreased by using minimal media containing glycerol, supplemented with a much less expensive inorganic nutrient source. It has been reported that minimal media containing only glycerol and inorganic salts could achieve 96.77% DHA production yields ( y sp ) (DHA moles per glycerol moles) . In addition to the use of an inorganic nitrogen and phosphorous source, this study uses crude glycerol to further minimize the cost of production.…”
Section: Introductionmentioning
confidence: 99%
“…There are only a limited number of articles published on this TU. It can produce high amounts of fructans and can efficiently produce glyceric acid from raw glycerol (Poljungreed and Boonyarattanakalin, ). It is an obligate aerobic acetic acid bacterium that is found as a spontaneous contaminant as part of the microbial community in some food processes (e.g.…”
Section: Assessmentmentioning
confidence: 99%
“…32 Among these, Gluconobacter strains have been used extensively in recent studies of DHA production as shown in Table 1. 23,32,34,35 Although the biological route can give excellent DHA selectivity, it has some limitations. The main challenge of DHA production is the inhibitory effect on bacterial growth due to the high concentrations of glycerol, 5,36 leading to the low DHA production capacity.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Commercial synthesis of DHA is preferred via the biological route as compared to the chemical route due to the nature of their microorganisms and the mild process environment. , The industrial strains for producing DHA from glycerol are Acetobacter species, Yeast species, and Gluconobacter species . Among these, Gluconobacter strains have been used extensively in recent studies of DHA production as shown in Table . ,,, Although the biological route can give excellent DHA selectivity, it has some limitations. The main challenge of DHA production is the inhibitory effect on bacterial growth due to the high concentrations of glycerol, , leading to the low DHA production capacity.…”
Section: Introductionmentioning
confidence: 99%